2019
DOI: 10.5114/aoms.2019.90470
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity expressed as a novel platelet reactivity score is associated with higher inflammatory state after coronary artery bypass grafting

Abstract: Introduction: Despite therapy, patients operated using a cardiopulmonary bypass demonstrate increased platelet aggregation, which rebounds to above preoperative levels. The aim of the study was to test the interaction between platelet reactivity/activation and selected inflammatory markers in the post-operative period. Material and methods: In total, 103 patients with non-ST elevation acute coronary syndrome (NSTE-ACS) who were not eligible for percutaneous coronary interventions (PCI), and required urgent rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…The absolute difference in MPA between these groups was only 2%, but it reached statistical significance (75% vs. 73%; p = 0.02). We found this result surprising, as we rather anticipated the opposite, as obesity causes the chronic low-grade inflammation of adipose tissue [38], and interactions between inflammation and elevated platelet aggregation have been previously described [21][22][23][24][25][26]. Indeed, our finding is inconsistent with other reports.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The absolute difference in MPA between these groups was only 2%, but it reached statistical significance (75% vs. 73%; p = 0.02). We found this result surprising, as we rather anticipated the opposite, as obesity causes the chronic low-grade inflammation of adipose tissue [38], and interactions between inflammation and elevated platelet aggregation have been previously described [21][22][23][24][25][26]. Indeed, our finding is inconsistent with other reports.…”
Section: Discussioncontrasting
confidence: 94%
“…Moreover, excessive platelet reactivity is a predictor of cardiovascular and all-cause mortality, and a risk equivalent to the presence of coronary artery disease in patients not receiving antiaggregatory therapy as well [21]. Finally, elevated concentrations of inflammatory markers, such as C-reactive protein (CRP), tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), or IL-10, correlate to higher platelet reactivity [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported different TNF plasma concentrations. The range is from a few [ 33 ] to several tens of pg/mL [ 34 ] in CAD patients, while in healthy people, it is about 2 pg/mL [ 35 ]. Our patients were all treated with statins, which reduce plasma TNF levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different authors report different levels of plasma TNF concentrations. The range varies from a few [39] to several tens of pg/mL [40] in people with CAD and approximately 2 pg/mL in healthy people [41]. Statins reduce plasma TNF levels [42], and our patients were all treated with statins.…”
Section: Tnf and Morphometry Parametersmentioning
confidence: 92%